Rola statystki publicznej w procesie monitorowania zrównoważonego rozwoju kraju. Aplikacja Wskaźniki Zrównoważonego Rozwoju w kontekście pomiaru jakości życia - Gorzelak, Monika (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
The present paper is concerned with measuring public health on the national level both as a determinant of life quality and as an area of sustainable development in its social dimension. The Sustainable Development Indicators Application is a publicly available tool for monitoring the condition of society. It was developed in the Statistical Office in Katowice in cooperation with the Statistical Office in Wroclaw, and launched on the official website of the Central Statistical Office of Poland in February 2016. The SDI Application is a proposal of official statistics for disseminating and presenting information on the sustainable development of the country. It includes a set of indicators grouped into areas within four domains: social, economic, environmental and institutional-political on the national, regional and local levels. SD indicators on the national list monitor goals referring to sustainable development, set out in national strategic documents, including quality of life, which underlies social, economic and institutional-political development of the country. Currently, the Polish SDI set is being further developed according to the guidelines outlined in the2030 Agenda adopted at the UN Summit in 2015.
Keywords: zrównoważony rozwój; wskaźniki zrównoważonego rozwoju; jakość życia; społeczeństwo; zdrowie